Study of Coffee Bean Displacement Inside Drum Roaster Using Force Balance Analysis - Hasbi Mubarak Suud; Noer Novijanto; Rufiani Nadzirah; Dyah Ayu Savitri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
The drum roaster's design and operating method significantly affect the coffee roasting process. The coffee bean displacement inside the drum roaster can be observed to compare the drum roaster's different designs and operating methods. The coffee bean movement is crucial since it affects the heat transfer distribution among coffee beans inside the drum roaster. The more dynamic displacement of coffee beans gives more even heat distribution. Force balance analysis can be used to predict the coffee bean displacement since it can predict particle movement with mutable variables. This paper compares the coffee bean displacement inside the drum roaster with flippers and without flippers using simple force balance analysis. The analysis involves tangential force, centrifugal force, frictional force, and the beans' weight itself. The analysis shows that the radius of the drum roaster (r) and angular acceleration (ω) significantly change the resultant force's dynamic, and the various tilt angle of flippers (β) did not too significantly affect it. The bigger radius (r) and angular acceleration (ω) generate a stronger centrifugal force influencing the bean's equilibrium. The direction change of force resultant applied to the bean is more smooth in the drum with flippers than without flippers. Keywords:  Coffee bean displacement, Drum coffee roaster, Force balance analysis, Resultant force Turning point duration